THE INFLUENCE OF CLIMATE FACTORS ON TOURIST VISITS IN PANGANDARAN COASTAL TOURISM AREA - ARIEF ROSYIDIE (Centre For Tourism Planning and Development, 2010)
One of the factors affecting tourism is the climatic conditions. It could become the attractiveness of tourism destinations, yet it can also interfere the performance of tourism in certain areas. In the last ten years, global climate have been changing, marked by changes in temperature, intensity and distribution of rainfall, wind speeds and patterns, etc. Climate change may impact tourism sector in various countries. Indonesia, as an archipelagic country and one of the world tourism destination, with various attractions, are vulnerable to climate change. One of the tourist destinations most vulnerable to climate change impacts is coastal tourism area. This paper discusses the phenomenon of climate change in Indonesia and the possible impact on coastal tourism from both, supply and demand sides. From the supply side, climate change could impact on coastal natural resource which has become the attraction of the coastal tourism, while from the demand side, climate change can affect the pattern of tourist visits to coastal tourism destinations. Although climate change and its impacts have not been felt by tourists and also managers of local tourism area, adaptation programs need to be proposed. Pangandaran beach tourism area, one of the leading and popular tourist destinations in West Java province, will be the focus of discussion in this paper.